Clinical Oncology Society of Australia position statement on exercise in cancer care. Issue 4 (7th May 2018) - Cormie, Prue; Atkinson, Morgan; Bucci, Lucy; Cust, Anne; Eakin, Elizabeth; Hayes, Sandra; McCarthy, Alexandra L; Murnane, Andrew; Patchell, Sharni; Adams, Diana
Abstract: Introduction: Clinical research has established exercise as a safe and effective intervention to counteract the adverse physical and psychological effects of cancer and its treatment. This article summarises the position of the Clinical Oncology Society of Australia (COSA) on the role of exercise in cancer care, taking into account the strengths and limitations of the evidence base. It provides guidance for all health professionals involved in the care of people with cancer about integrating exercise into routine cancer care. Main recommendations: COSA calls for: exercise to be embedded as part of standard practice in cancer care and to be viewed as an adjunct therapy that helps counteract the adverse effects of cancer and its treatment; all members of the multidisciplinary cancer team to promote physical activity and recommend that people with cancer adhere to exercise guidelines; and best practice cancer care to include referral to an accredited exercise physiologist or physiotherapist with experience in cancer care. Changes in management as a result of the guideline: COSA encourages all health professionals involved in the care of people with cancer to: discuss the role of exercise in cancer recovery; recommend their patients adhere to exercise guidelines (avoid inactivity and progress towards at least 150 minutes of moderate intensity aerobic exercise and two to three moderate intensity resistance exercise sessions each week); and refer their patients to a health professional who specialises in the prescription and delivery of exercise (ie, accredited exercise physiologist or physiotherapist with experience in cancer care).